Post-flood social support networks and morbidity in Jôsô City, Japan. (January 2019) - Lebowitz, Adam; Tachikawa, Hirokazu; Aiba, Miyuki; Okamoto, Yuta; Takahashi, Sho; Nemoto, Kiyotaka; Arai, Tetsuaki
Highlights: Global warming has increased frequency of river flooding from extreme weather. Disaster survivors can suffer mentally from depression and stress. Social support can help post-disaster mental health, but effects are complex. Support source, and providing or receiving support can have different effects. Understanding support network complexity can help future disaster planning. Abstract: Social support networks are considered beneficial for post-disaster survivor mental health. However, there are family and non-family networks, and support can be received or provided. Therefore, their complex contribution to wellbeing requires analysis. Researching elderly residents of Jôsô City NE of Tokyo ( N = 1182 [female: n = 618], Age M = 69.76y, SD = 6.10y) who experienced severe flooding in September 2015 investigated data for mental health outcomes of depression (K6), trauma (IES-R), and existence of recent worry from evacuation and house damage. An original instrument tapped support source and direction, controlled to examine mental health symptom changes. House damage was a higher mental health predictor (ηp 2 = .10–.16) than evacuation (ηp 2 = .033–.093). Results indicated family social support may buffer mental health outcomes, but non-family social support may burden them. Overall support network size also indicated burdening compared to social support receiving-providing imbalance.